University professors’ level of performance in the use of Artificial Intelligence. - De Obesso, María de las Mercedes; Núñez Canal, Margarita; Pérez Rivero, Carlos Alberto; Álvarez de Mon, Ignacio (Universidad Complutense de Madrid, 2025)
The European Union is promoting digitalization as a means to increase the competitiveness of its economy and improve education systems according to new demands. As a result, universities need to take strategic action to adapt to this new reality. The purpose of this research is to measure professors' proficiency in using Artificial Intelligence (AI) by developing a valid questionnaire based on the DigCompEdu tool, which assesses AI competency. The research question aims to examine the correlation between university professors' AI performance and its impact on teaching activity. Four hypotheses are posed, two related to the learning and development of digital competencies in students and two linked to the regulatory framework and the ethical implications. All hypotheses have been confirmed, and the following conclusions have been reached. Firstly, it has been found that professors have low performance in using AI tools beyond ChatGPT or translation tools. Secondly, professors lack confidence in their AI competence when applied to teaching and research. Thirdly, educational institutions are not investing in AI training to develop the AI competence of educators. Higher education institutions have a crucial responsibility to meet the challenges and risks associated with the use of AI. They must ensure that AI is used ethically, academic integrity is maintained, and that they do not fall behind in their efforts to train professors and prepare students with the digital skills required for the job market.
Keywords: 53 Ciencias Económicas::5312 Economía sectorial::5312.04 Educación; ODS 4 - Educación de calidad; Higher Education; AI literacy; AI educators’ competence; digital competence